2010
DOI: 10.1186/1465-9921-11-138
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylthiourea protects against chlorine induced changes in airway function in a murine model of irritant induced asthma

Abstract: BackgroundExposure to chlorine (Cl2) causes airway injury, characterized by oxidative damage, an influx of inflammatory cells and airway hyperresponsiveness. We hypothesized that Cl2-induced airway injury may be attenuated by antioxidant treatment, even after the initial injury.MethodsBalb/C mice were exposed to Cl2 gas (100 ppm) for 5 mins, an exposure that was established to alter airway function with minimal histological disruption of the epithelium. Twenty-four hours after exposure to Cl2, airway responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…In addition to preventing neutrophil influx and changes in KC, DMTU completely prevented AHR in Rn and H. However, DMTU was unable to prevent AHR in G. Similarly, Shalaby et al (39) demonstrated that DMTU prevented neutrophil accumulation in BAL fluid as well as AHR in both the central and peripheral lung compartments in an allergic model of asthma in mice exposed to birch pollen extract. In a model of irritant-induced asthma using Cl 2 gas, DMTU was also effective in reducing AHR in both peripheral and central lung (25). Our findings suggest a role for oxidative stress, likely associated with neutrophil populations, following OD exposure.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to preventing neutrophil influx and changes in KC, DMTU completely prevented AHR in Rn and H. However, DMTU was unable to prevent AHR in G. Similarly, Shalaby et al (39) demonstrated that DMTU prevented neutrophil accumulation in BAL fluid as well as AHR in both the central and peripheral lung compartments in an allergic model of asthma in mice exposed to birch pollen extract. In a model of irritant-induced asthma using Cl 2 gas, DMTU was also effective in reducing AHR in both peripheral and central lung (25). Our findings suggest a role for oxidative stress, likely associated with neutrophil populations, following OD exposure.…”
Section: Discussionmentioning
confidence: 56%
“…*P Ͻ 0.05, **P Ͻ 0.01, and ***P Ͻ 0.001; n ϭ 5-6/group. burden, we utilized an antioxidant, DMTU, that has been shown to prevent pulmonary neutrophilia following inhalation of chlorine gas (25). We found that DMTU prevented ODinduced airway inflammation in lung tissue and prevented neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorine exposure produces changes in lung function, including altered airway resistance, elastance, and reactivity to methacholine (7, c P Ͻ 0.01 vs. corresponding unexposed; d P Ͻ 0.05 vs. corresponding unexposed. 10,13,24,26,35,40). These changes are complex and appear to depend on the dose of chlorine as well as the species and strain of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…At the age of 12 wk, airway responsiveness to methacholine challenge was measured as described by McGovern et al (27). The mice were anesthetized and paralyzed using i.p.…”
Section: Airway Responsivenessmentioning
confidence: 99%